Resin Yield Potential of Chir Pine (Pinus roxburghii Sargent) - Verma, V. P. S.; Payal, P. S. (Indian Forester, 1976)
The paper gives the data of resin yield obtained from various numbers of 20 cm and 40 cm wide blazes as compared to 10 cm wide blaze from 1972 to 1974. The data from untreated blazes as well as those treated with a 20% mixture of Sulphuric and nitric acids is given. The maximum average yield obtained during 3 years from untreated blazes was 13.225 kg per tree and from the treated blazes was 17.268 kg per tree which was obtained when 45.8% and 61.4% of the girth from untreated and treated trees respectively was wounded. More than one narrow blaze together yield more resin than a single blaze of equivalent width.